PROTECCIÓN DE LA MUJER TRABAJADORA FRENTE A ACTOS EMPRESARIALES DISCRIMINATORIOS DURANTE EL PERÍODO DE PRUEBA DEL CONTRATO DE TRABAJO. MARCO CONSTITUCIONAL Y ÁMBITO LEGAL - Gallegos Moya, Fermín (Revista de Derecho, 2019)
During the probationary period of the employment contract, and provided that it has been established according to the legal and conventional requirements regulating it, the termination of the contract (withdrawal) may be produced unilaterally by both contracting parties, without the need for allegations, much less accreditation, of the reasons for the termination. This undemanding cause and the alleged legitimacy surrounding the decision cannot, however, protect the exercise of an extinctive faculty that harms fundamental rights such as equality and non-discrimination of working women. In this work we will analyse the marked differences in the protective scope of these fundamental rights that derive from a mere temporary element: the overcoming or not, in agreeing to the termination, of the time established as a probationary period, to the extent that such protective framework remains “weakened” while the initial phase of the contract has not ended.